Neutron diffraction from superparamagnetic colloidal crystals. (November 2017) - Ličen, M.; Drevenšek-Olenik, I.; Čoga, L.; Gyergyek, S.; Kralj, S.; Fally, M.; Pruner, C.; Geltenbort, P.; Gasser, U.; Nagy, G.; Klepp, J.
Abstract: We fabricated a superparamagnetic ordered structure via self-assembly of a colloidal crystal from a suspension of maghemite nanoparticles and polystyrene beads. Such crystals are potential candidates for novel polarizing beam-splitters for cold neutrons, complementing the available methods of neutron polarization. Different bead sizes and nanoparticle concentrations were tested to obtain a crystal of reasonable quality. Neutron diffraction experiments in the presence of an external magnetic field were performed on the most promising sample. We demonstrate that the diffraction efficiency of such crystals can be controlled by the magnetic field. Our measurements also indicate that the Bragg diffraction regime can be reached with colloidal crystals.